Coordination Behaviour Of 2-Hydroxybenzoic Acid Hydrazide Towards Nickel (II) And Cobalt(II): Spectroscopic Investigation - Bajracharya, Purnima; Shrestha, Sabita (Scientific World, 2021)
Four coordinated Nickel and six coordinate Cobalt complexes of type [Ni (HBH)2]. 2Cl, and Co (HBSH)2Cl2]Cl.2H2O [2-HBH=2-Hydroxybenzoic acid hydrazide] respectively were synthesized. The coordination behavior of 2-HBH in complexes have been suggested on the basis of analytical and spectroscopic techniques, where the ligand is coordinating to metal through oxygen of carbonyl and nitrogen of terminal NH2 group. All the complexes are coloured and non-hygroscopic. The compositions of complexes were established on the basis of various analytical procedures. The molar conductance value shows 1:1 electrolyte in Co (II) complex and 1:2 in Ni (II) complex. The electronic spectral studies showed the square planner geometry around Ni(II) and octahedral geometry around the Co (II) ion. The optical band gap energy of complexes was derived from electronic spectra the value of which underlies the range of semiconductor materials.